The contribution of assisted coral restoration to calcium carbonate production in Eastern Pacific reefs - Tortolero-Langarica, J. J. Adolfo (2023)
Introduction: Hermatypic corals have the capacity to construct the physical reef-framework and maintain the balance of coral reef functionality. However, in the past three decades, coral communities have been menaced by natural and anthropic pressures, resulting in an abrupt coral cover decline, and slow natural recovery.  To mitigate coral reef collapse, assisted restoration techniques has been implemented and improved worldwide, However, the long-term effects of such interventions on ecological attributes have been scarcely reported.  Objective: This study evaluated the effect of assisted coral intervention on calcium carbonate production (kg CaCO3 m-2 yr-1) and ecological volume (cm3) yielded by branching and massive corals from the central Mexican Pacific.  Methods: We used colony size, extension rate, and skeletal density measurements of direct outplanted Pocillopora and Pavona coral species to calculate coral carbonate production, ecological volume, and model their long-term potential.  Results: Coral carbonate produced after one-year of outplanting increased by 42 % (1.17 kg CaCO3 m-2 yr-1), where Pocillopora spp. and Pavona clavus corals contribute with 0.97 and 0.20 kg CaCO3 m-2 yr-1, respectively. The ecological volume also increased by 384 cm3 for Pocillopora and 56 cm3 for Pavona after one year period. Furthermore, the results suggest that long-term coral restoration actions (10 years) have the potential to significantly increase carbonate production.  Conclusions: our data indicate that coral restoration initiatives have the potential to help mitigate the current low calcium carbonate production of Mexican Pacific reefs and may significantly contribute to the long-term maintenance of reef-framework based on ecological engineering tools, such initiatives represent essential functional properties related to reef ecosystem services provision.